2021
DOI: 10.12688/f1000research.73060.1
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid recommender system based on data enrichment on the ontology modelling

Abstract: Background: A recommender system captures the user preferences and behaviour to provide a relevant recommendation to the user. In a hybrid model-based recommender system, it requires a pre-trained data model to generate recommendations for a user. Ontology helps to represent the semantic information and relationships to model the expressivity and linkage among the data. Methods: We enhanced the matrix factorization model accuracy by utilizing ontology to enrich the information of the user-item matrix by integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…When comparing the papers with respect to their metrics, our work outperforms all the papers by a wide range, with the exception of (Selvan et al, 2019), where our work is better in the Precision metric and inferior in the Recall and F 1‐measure metrics, but it can also be observed that these difference are minimal. It is also important to highlight that there is no previous work that evaluates the quality of the generated ontology (see works, Chew et al, 2021; Mahdi & Hadi, 2021; Selvan et al, 2019), only McSherry (2006) and our work proposes a metric to evaluate it (completeness).…”
Section: Analysis Of Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…When comparing the papers with respect to their metrics, our work outperforms all the papers by a wide range, with the exception of (Selvan et al, 2019), where our work is better in the Precision metric and inferior in the Recall and F 1‐measure metrics, but it can also be observed that these difference are minimal. It is also important to highlight that there is no previous work that evaluates the quality of the generated ontology (see works, Chew et al, 2021; Mahdi & Hadi, 2021; Selvan et al, 2019), only McSherry (2006) and our work proposes a metric to evaluate it (completeness).…”
Section: Analysis Of Resultsmentioning
confidence: 98%
“…They use a social LD platform to design a fully decentralized and privacy‐aware platform that supports interoperability and care integration. Chew et al (2021) define a hybrid model‐based recommender system, which is pre‐trained with data to generate recommendations for a user using an ontology that helps to represent the semantic information and relationships to model the expressivity and linkage among the data. They define a matrix factorization model accuracy by utilizing the ontology to enrich the information of the user‐item matrix by integrating the item‐based and user‐based collaborative filtering techniques.…”
Section: Related Workmentioning
confidence: 99%
“…3) Hybrid Filtering Technique: Real-world recommender systems usually combine the best features among several recommendation techniques into a hybrid technique to increase performance and overcome limitations in each technique. Based on the hybrid techniques, the advantages of one algorithm might be outweighed by the disadvantages of another algorithm, resulting in better suggestions than those provided by a single algorithm [21]. Multiple recommendation approaches can be employed to conceal the flaws of each individual recommendation strategy in a combined model.…”
Section: ) Collaborative Filtering Techniquementioning
confidence: 99%